Far upstream element-binding protein 1 facilitates hepatocellular carcinoma invasion and metastasis. (7th October 2019) - Fu, Pei-Yao; Hu, Bo; Ma, Xiao-Lu; Tang, Wei-Guo; Yang, Zhang-Fu; Sun, Hai-Xiang; Yu, Min-Cheng; Huang, Ao; Hu, Jin-Wu; Zhou, Chen-Hao; Fan, Jia; Xu, Yang; et al.
Abstract: Previous research suggests that far upstream element-binding protein 1 (FUBP1) plays an important role in various tumors including epatocellular carcinoma (HCC). However, the role of FUBP1 in liver cancer remains controversial, and the regulatory pathway by FUBP1 awaits to be determined. This study aims to identify the role of FUBP1 in HCC progression. Our result shows that the high level of FUBP1 expression in HCC predicts poor prognosis after surgery. Overexpression of FUBP1 promotes HCC proliferation, invasion, and metastasis by activating transforming growth factor-β (TGF-β)/Smad pathway and enhancing epithelial-mesenchymal transition (EMT) in vitro and in vivo . Inhibitor of Thrombospondin-1 (LSKL) could inhibit HCC proliferation and invasion in vitro and in vivo by blocking the activation of TGF-β/Smad pathway mediated by thrombospondin-1 (THBS1). Our study identified the critical role of FUBP1-THBS1-TGF-β signaling axis in HCC and provides potentially new therapeutic modalities in HCC.